Surgical Quality Improvement - Kelz, Rachel R.; Wong, Sandra L. (Springer International Publishing : Imprint: Springer, 2017)
This unique handbook is designed for surgeons involved in personal, programmatic, institutional, regional or national QI efforts. The book highlights key quality improvement principles that relate to the care of the surgical patient. Theories as well as practical tips regarding quality improvement are gathered for this outstanding resource. Aimed at surgical residents and young surgical faculty, Success in Academic Surgery: Surgical Quality Improvement is written by expert authors who are members of the Association for Academic Surgery. No similar book directed at surgeons exists, and this is a timely and comprehensive QI resource for trainees, educators, and surgical leaders.- Resumé vydavatel
Keywords: chirurgie; surgery; elektronické knihy; kolektivní monografie; electronic books; collective monographs